2019
DOI: 10.1016/j.ssci.2019.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Integration of multiple methods in identifying patient safety risks

Abstract: There is a growing awareness that risk identification plays an important role in the investigation of actual and potential harm to patients. Although current risk identification methods in healthcare have strengths and limitations, it is an open question whether they have been implemented optimally and how well they have been integrated to provide a complete picture of risk within complex healthcare systems. To shed light on this, this paper reviews the characteristics of reactive and proactive risk identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 73 publications
(101 reference statements)
0
13
0
Order By: Relevance
“…Globally, there is recognition that health providers should undertake a comprehensive assessment of patient safety risks, which are often managed through organisational clinical documentation (Simsekler et al, 2019 ). The benefits of a comprehensive multidimensional assessment are to detect risks and identify care needs to inform interventions and plans of care to improve patient outcomes (Ellis et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, there is recognition that health providers should undertake a comprehensive assessment of patient safety risks, which are often managed through organisational clinical documentation (Simsekler et al, 2019 ). The benefits of a comprehensive multidimensional assessment are to detect risks and identify care needs to inform interventions and plans of care to improve patient outcomes (Ellis et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“… 35 , 36 The very slow and sporadic adoption of PHA approaches in both laboratories could be due to lack of expertise in healthcare, lack of training, time-intensive, and the absence of office for ergonomic safety. 37 In support of this current finding, a recent study conducted at a UK based hospital showed that the healthcare staff had few experienced using PHA to identify risks prospectively valuable challenges such as insufficient training, time, and staff constraints. 5 …”
Section: Discussionmentioning
confidence: 59%
“…These methods facilitate learning from past experiences, implementing roost cause analysis (RCA), and providing a benchmarkable dataset on past risks. 37 The current data demonstrated that both laboratories were missing the following documents (n=7), previous incident report, incident report file, equipment inventory, equipment maintenance file, chemical inventory list, bacterial strain (for microbiology lab), and waste management SOP. Based on the incident investigation (retrospective method), both microbiology and hematology laboratories do not record incidents besides incident report sheets.…”
Section: Discussionmentioning
confidence: 81%
“…The present study also found that the healthcare team, including the nurses, observed patient safety issues and made every effort to provide a safe model to achieve specific care goals in a targeted manner. According to the literature, nurses have always solved problems in a targeted manner by focusing on them and using detailed plans and effective measures [ 43 ]. One of these targeted cases is crisis management during home emergencies.…”
Section: Discussionmentioning
confidence: 99%